The Contribution of Organizational Citizenship Behavior, Self-Efficacy, and Interpersonal Communication to Teacher Performance - Linda Kahar; Muliha Halim; La Ode Amaluddin; La Ili (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study aims to analyze and describe the contribution of organizational citizenship behavior, self-efficacy, and interpersonal communication to the performance of Guidance and Counseling (BK) teachers. The survey was used as a technique in this quantitative research. Guidance and Counseling teachers in Kendari City State Vocational/Advanced High Schools, totaling 60 teachers, became the population in the study. The sample was determined by the total sampling technique, which made the entire population the sample in the study. Questionnaires and interviews were used to collect data. Descriptive and inferential statistics through multiple regression tests are techniques in data analysis. Through the research, it is concluded that organizational citizenship behavior significantly contributes to the performance of counseling teachers in Kendari City State Vocational High Schools, self-efficacy significantly contributes to the performance of counseling teachers in Kendari City State Vocational High Schools, interpersonal communication significantly contributes to the performance of counseling teachers in Kendari City State Vocational High Schools, and organizational citizenship behavior, self-efficacy, and interpersonal communication together significantly contribute to the performance of counseling teachers in Kendari City State Vocational High Schools.